Printing Wearable Devices in 2D and 3D: An Overview on Mechanical and Electronic Digital Co-design - Tansaz, Samira; Baronetto, Annalisa; Zhang, Rui; Derungs, Adrian; Amft, Oliver (IEEE Pervasive Computing, 2019)
Multiprocess Additive Manufacturing (AM) offers system designers new, exciting computational tools to rapidly realise smart wearable sensing devices in two-dimensional (2D) and 3D shapes. We guide readers through the novel development and fabrication process based on a digital co-design framework and highlight AM techniques, functional materials, and assembly procedures for designing wearables as flexible and stretchable on-skin patches, e-textiles, and smart accessories for everyday use.
CRIS-Team Scopus Importer:2019-12-20
Keywords: Fabrication; Ink; Printing; Substrates; Three-dimensional displays; Tools; Two dimensional displays